Evaluation of Fluorescent Cu2+ Probes: Instant Sensing, Cell Permeable Recognition and Quantitative Detection - Hao He; Zhao Cheng; Lei Zheng; Xuejiao Zhang (Molecules, 2021)
By incorporating a rhodamine spirolactam structure as the recognition site for Cu2+, two novel probes were synthesized through a connection of rhodamine 6G acylhydrazine and 5-formyl-6-hydroxyl-4-methylcoumarin/2,4-dihydroxybenzaldehyde. In the recognition process of probes towards Cu2+, the spirolactam ring exhibited opening and closing, accompanying an instant and specific change in fluorescence and in color, which could also achieve a naked-eye and semiquantitative recognition of aqueous Cu2+ besides the fluorescent Cu2+ detection method. Fluorescent analyses and ECV304 cell imaging further revealed the probes’ good optical stability, instant response, low toxicity, and membrane permeability, which offers future possibilities for the probes’ instant detection and the real-time tracking of Cu2+ in biological systems.